Participatory Methodology with an Intercultural and Intergenerational Approach: An Educational Experience in the City - Gallardo-López, José Alberto; Muñoz Villaraviz, David (IJERI: International Journal of Educational Research and Innovation, 2021)
This research includes a teaching experience within the framework of an educational innovation project of the Junta de Andalucía, whose backbone is an Annual Communication Sample (MuAC) that, after three editions, has consolidated as a meeting place for educators and students of all ages, different cultures, and socio-educational realities. The main objective is to turn students into the protagonist of their learning, in inter- regional and intercultural contexts, besides showing and sharing sound educational practices in emblematic areas of the city. This way, people involved exchange their experiences with teachers through participatory methodologies that favor meaningful learning.They also make visible the multiple innovative educational tasks that are carried out in their educational centre. The study basically analyzes from a quantitative methodology, information collected in the three editions of the MuAC and establishes a comparison, in which the number of participants for year of publication are reflected, educational levels, educational institutions participating, the whole workshops and socio-educational activities carried out, and the degree of satisfaction with the experience. After analysis, we conclude that lt was a highly satisfactory experience, we involved in the edition of 2018 more than 1000 students, and 87 teachers from 12 different schools, 9 secondary schools, 1 University, and 12 socio - educational organizations. This type of activity improves social relationships, helps to promote teaching and learning from an intercultural and intergenerational approach, and expands the concept of the neighborhood among the citizenship that has been participating in this experience.